A Decade of Breastfeeding Self-Efficacy Research: A Bibliometric Analysis using VOSviewer - Maulida, Luluk Fajria; Novika, Revi Gama Hatta; Wahidah, Nurul Jannatul; Maulina, Rufidah; Nurhidayati, Siti; Sari, Atriany Nilam; Richa, Fadhila Tsania (Faculty of Medicine Universitas Sebelas Maret, 2025)
Introduction : A mother’s confidence in her ability to breasfeed, known as breastfeeding self efficacy (BSE) is a key predictor of exclusive breastfeeding duration. This study aimed to analyze the development of BSE research and provide insights for researchers and policymakers to improve future studies.Method : This bibliometric analysis was conducted using data from the Scopus database, one of the largest sources of peer reviewed literature. Articles were retrieved on August 7, 2024, using the keywords “Breastfeeding” AND “Self” AND “Efficacy.” A total of 1,006 documents were identified. After applying inclusion criteria (English language, article or review type, published between 2014 and 2023, open access, and final publication stage), 413 documents were selected for analysis. Data were analyzed using VOSviewer version 1.6.20 based on publication year, journal source, author, country of origin, and keywords.Results : Research on BSE has shown a consistent upward trend over the past decade, with the highest number of publications in 2023 (82 articles). The United States was the most productive country, followed by Brazil, Canada, the United Kingdom, China, and Indonesia. Most articles were published in journals focusing on lactation physiology, breastfeeding challenges, and evidence based interventions. The most cited studies emphasized the importance of partner support, coparenting, and breastfeeding safety during the COVID-19 pandemic. Keyword analysis revealed several underexplored areas, particularly the role of midwives, formula use, and BSE in mothers of preterm infantsConclusion : This study highlights the growing global attention to breastfeeding self-efficacy as a key factor in improving maternal and child health, and points to the need for further research on underexplored areas, including the role of midwives and the impact of alternative feeding practices, to support more effective interventions and policies.